THE IMPACT OF PRICE AND PRODUCT QUALITY ON THE DECISION TO PURCHASE MIXUE PRODUCTS AMONG SURABAYA STUDENTS - Nindya Kartika Kusmayati; Yuli Kurniawati; Safa’at; Noneng R. Sukatmadiredja (Jurnal Mebis, 2024)
This research aims to evaluate whether price and product quality have an influence on purchasing decisions for Mixue products. The data analysis was carried out using the multiple linear regression method using SPSS software. This research involved 58 students as research samples. This sample was selected using a non-probability sampling technique with a saturated sampling approach. The findings of this research can be summarized as follows: First, price has a positive and significant effect on purchasing decisions for Mixue products. Second, product quality also has a positive and significant influence on the decision to purchase Mixue products. Third, both price and product quality, when considered simultaneously, have a significant influence on the decision to purchase Mixue products. Thus, the implication of this research is that both price and product quality can have a positive impact on prospective buyers' purchasing decisions for Mixue products.